Targeting urban malnutrition: a multi-city analysis of the spatial distribution of childhood nutritional status - Morris, Saul Sutkover (International Food Policy Research Institute, 2000)
This article examines the degree to which child malnutrition, infectious disease, and mortality, as well as poverty, overcrowding, substandard housing, and lack of access to basic services, tend to concentrate in particularly disadvantaged neighborhoods in developing country cities. Findings are presented for seven cities in Africa, Asia, and Latin America.